Creating Interactive Online Learning Experiences among Secondary School Students in Lagos State, Nigeria. - Moses Odo (Universitas Ahmad Dahlan, 2022)
In the recent time teaching and learning is no more confined to face-to-face exercise where the students are mere listeners instead of fully participate in the class activities. The study is on creating interactive online learning experiences among Secondary School students in Lagos State, Nigeria. It was a survey study and the population for the study included all the teaching staff members of all the Public Senior Secondary School in Shomolu Local Government Area. Random sampling technique was used to select 100 teachers who responded to the developed questionnaire. A structured questionnaire containing 40 questionnaire items were developed on four point scales. The response scale for the questionnaire is Strongly Agree (4), Agree (3), Disagree (2) and Strongly Disagree (1). The questionnaire was face validated while the reliability of the test was determined using test re-test procedure. The findings of the indicated that there are number ways which online learning can be made interactive. These ways include: involving feedback, creating interactive activities, Assignments & Breakout groups, exploring other free ICT tools, limiting seat time, good teachers/student relationship, discourage absenteeism, allow few minutes of jokes among students during classroom activities and creating course content that is engaging and encouraging peer. Teachers and students related challenges to effective and interactive online learning include lack of motivation in online learners, technical difficulties with online teaching tools, time-consuming resources, setting and forgetting online learning activities, poor learning outcomes, lack of appropriate devices, poor learning space at home, stress among students, lack of fieldwork and access to laboratories and loneliness. It was recommended that creating interactive online learning experiences among secondary school students in Lagos State, could be through involving feedback, creating interactive activities, assignments and breakout groups, exploring other free ICT tools, limiting seat time and good teachers/student relationship.